2018
DOI: 10.2337/dc17-2108
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gut Microbiota–Related Metabolites and Long-term Successful Weight Loss in Response to Weight-Loss Diets: The POUNDS Lost Trial

Abstract: Overweight and obese individuals who showed decreases in circulating choline or l-carnitine levels achieved greater improvements of adiposity and energy metabolism by eating a low-calorie weight-loss diet, suggesting that such metabolites are predictive of individuals' response to the treatment. Further investigations are necessary to confirm our findings, particularly in a population with prediabetes that is more representative of the U.S. population with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 43 publications
8
52
2
Order By: Relevance
“…There were no significant differences in mean values of body mass index (BMI), fasting glucose, fasting insulin and the homeostasis model assessment of insulin resistance (HOMA-IR) at the baseline examination between participants who were included (n=510) or those who were not included (n=301) in the present analysis. As we described previously,26 the baseline median (25th, 75th) values of each metabolite were 2.7 (1.8, 3.8) µM for TMAO, 8.6 (7.4, 10.3) µM for choline and 34.5 (30.0, 39.3) µM for L-carnitine among the 510 participants. Since a few participants (n=6) had missing data on fasting insulin, haemoglobin A1c (HbA1c) or 6-month changes in serum amino acid metabolites, these were excluded from the present analysis.…”
Section: Methodssupporting
confidence: 57%
See 4 more Smart Citations
“…There were no significant differences in mean values of body mass index (BMI), fasting glucose, fasting insulin and the homeostasis model assessment of insulin resistance (HOMA-IR) at the baseline examination between participants who were included (n=510) or those who were not included (n=301) in the present analysis. As we described previously,26 the baseline median (25th, 75th) values of each metabolite were 2.7 (1.8, 3.8) µM for TMAO, 8.6 (7.4, 10.3) µM for choline and 34.5 (30.0, 39.3) µM for L-carnitine among the 510 participants. Since a few participants (n=6) had missing data on fasting insulin, haemoglobin A1c (HbA1c) or 6-month changes in serum amino acid metabolites, these were excluded from the present analysis.…”
Section: Methodssupporting
confidence: 57%
“…On the other hand, L-carnitine supplementation has been suggested to improve glycaemic control in patients with type 2 diabetes 46. We have recently reported that changes in choline and L-carnitine were significantly associated with improvements in adiposity measurements 26. In the present study, we found that the adjustment for concurrent weight changes weakened the associations of choline or L-carnitine with insulin resistance.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations